2007
DOI: 10.2337/dc06-1688
|View full text |Cite
|
Sign up to set email alerts
|

How Reliable Is Estimation of Glomerular Filtration Rate at Diagnosis of Type 2 Diabetes?

Abstract: OBJECTIVE -The Cockcroft-Gault (CG) and Modification of Diet in Renal Disease (MDRD) equations previously have been recommended to estimate glomerular filtration rate (GFR). We compared both estimates with true GFR, measured by the isotopic 51 Cr-EDTA method, in newly diagnosed, treatment-naïve subjects with type 2 diabetes.RESEARCH DESIGN AND METHODS -A total of 292 mainly normoalbuminuric (241 of 292) subjects were recruited. Subjects were classified as having mild renal impairment (group 1, GFR Ͻ90 ml/min p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…A larger study might have revealed other subgroups likely to benefit more from fenofibrate. Renal assessment through inulin and p-amino hippurate clearance is impractical in large trials and estimated GFR has limitations [13]. Nevertheless, comparative temporal within-patient changes in estimated GFR and particularly plasma creatinine in our large sample are likely to remain robust [43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A larger study might have revealed other subgroups likely to benefit more from fenofibrate. Renal assessment through inulin and p-amino hippurate clearance is impractical in large trials and estimated GFR has limitations [13]. Nevertheless, comparative temporal within-patient changes in estimated GFR and particularly plasma creatinine in our large sample are likely to remain robust [43].…”
Section: Discussionmentioning
confidence: 99%
“…Although estimated GFR may underestimate true glomerular filtration rate [13], particularly at >90 ml min Patients were seen at intervals of 4 to 6 months against a background of usual care, and information on treatment toleration and complications was obtained. Urinary albumin and creatinine were measured pre-randomisation (the mean of two first morning samples) and at year 2, year 5 and close-out.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several equations have been developed for estimating GFR. The Modified Diet in Renal Disease (MDRD) Study equation underestimates GFR, particularly in patients with GFR >90 ml/min/1.73m 2 [72]. The Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation appears to be more accurate than the MDRD equation in estimating GFR, particularly at higher GFR [73][74][75].…”
Section: Diagnosis Of Diabetic Nephropathymentioning
confidence: 99%
“…In group MS between MDRD and AU we not observed a correlation (p=0.263) Figure 3, but with between CG and AU there was a incorrect positive relationship (p=0.001=) Figure 4. In general, these studies show good performance in people with MS. Two studies, comparing the CG and MDRD formulae to a measured GFR, found that the MDRD formula was more precise and accurate than the CG formula in people with MS (14). In comparing with the normal population, MS is accepted like a independent risk factor for CKD.…”
Section: Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi Turkish Nementioning
confidence: 99%